FRI0761-HPR Chronic widespread pain prevalence in the general population: a systematic review & meta-analysis. (15th June 2017) - Andrews, P; Steultjens, M; Riskowski, J
Abstract : Background: Chronic widespread pain (CWP) is a worldwide health problem and a significant contributor to disability. Understanding the impact of individual-dependent (e.g., gender) and contextual-dependent (e.g., survey method, latitude) factors have on CWP prevalence may provide a foundation population-based strategy for addressing CWP. Objectives: To determine a general population worldwide estimate of CWP prevalence and to examine the individual and contextual-dependent factors related to CWP prevalence. Methods: A systematic review was undertaken using seven databases. Along with data extracted from the manuscripts, additional contextual data including WHO development status and region, human development index (HDI; measure of socioeconomic position), GINI coefficient (measure of inequality), and latitude were added. Methodological reporting quality was assessed using the STROBE checklist [1]. Meta-analyses were conducted to determine global CWP prevalence, and individual- and contextual-dependent factors were evaluated using meta-regression analyses. Results: Thirty studies across 20 countries (630, 654 participants) met the inclusion criteria. Studies varied in CWP diagnostic criteria, survey method, and reporting quality. Study CWP sample prevalence ranged from 1.4–24.0%, with CWP in men ranging from 1.1–15.3%, while in women it ranged from 1.7–22.1%. Estimated overall CWP prevalence was 9.4% (7.6–11.3%). By gender, the global CWP prevalence estimate in women was significantly higher than for men (10.9% [8.1–13.7%] v 6.7% [4.5–8.8%], p≤0.01; Table). A meta-regression of the contextual factors showed the HDI was related to CWP prevalence (p=0.002), while other measures such as survey type, methodological reporting quality and GINI index showed no significant effect. Conclusions: Globally CWP affects one in ten individuals within the general population, with women more likely to experience CWP than men. HDI was noted to be the socioeconomic factor related to CWP prevalence, with those in more developed countries having a lower CWP prevalence than those in less developed countries. There was a lack of data from countries with a lower socioeconomic position, and further CWP data in these areas can help determine if there are socioeconomic effects associated with CWP prevalence and can refine the CWP prevalence estimate. References: Poorolajal, J., et al., Epidemiology and health, 2011. 33. Disclosure of Interest: None declared